An approach for identification of mode in micro grooving of sintered alumina. (26th March 2012) - Giridhar, D.; Vijayaraghavan, L.; Krishnamurthy, R.
New materials usually require new manufacturing processes to create the final shape, with desired bulk and surface properties. The knowledge of the mode of material removal of these new materials in manufacturing is required for better understanding of material removal mechanism. In the present work, the change in mode of grooving in alumina ceramic material is studied in a micro grooving operation. The responses from the dynamics of the grooving process, such as horizontal cutting force and extrinsic parameters (depth, width and aspect ratio of the groove) were taken into account. Time domain and frequency domain responses of the material from the acoustic emission (AE) sensor from different grooving conditions are taken into consideration as the intrinsic response of the material. A strategy has been adopted for windowing and fast Fourier transform operations for extracting time domain and frequency domain responses to effectively characterise the raw AE signal. The grooving operation was done at different levels of normal load, angle of inclination and grooving speed. Correspondence between responses of dynamics of the grooving process and intrinsic responses from AE helps to understand the material removal mechanisms of the process.